Manejo de residuos sólidos hospitalarios del centro de salud Soritor - Silva Piña, Sandy Katheryn (2010)
In the Soritor Health Center the work of managing of the Hospitable Solid Residues is slightly frequent, for what it is necessary be in constant training not only focus on the cleaning staff if not to all the staff that works in the Center has already mentioned, why most of his time spend in their place of employment, are in direct contact with the patients what they want to say that diseases can more easily. The logistics area does not have the necessary materials for the protection of the cleaning staff, the workers on their part, must require the network of health that provide them with suitable materials for the correct development of the solid waste management and so avoid accidents and pollution in the Health Center. The health center must take into account how important it is to be the path we will pick you up from the waste and the proper time zone to avoid that patients have direct contact with these residues. lt is important that the cleaning staff count with the clothing (clothing) and appropriate equipment as containers with wheels to make your work and so avoid the direct contact with the Waste and acquire any disease. The solid waste management monitoring must be constant so that the personnel working in the Center take as part of your routine work the proper waste handling in such a way that is no longer something tedious perform such work. Key words: Hospitable Solid Residues, solid waste management.